Behavioral and neuroendocrine consequences of disrupting a long-term monogamous social bond in aging prairie voles. (4th May 2021) - Grippo, Angela J.; McNeal, Neal; Normann, Marigny C.; Colburn, William; Dagner, Ashley; Woodbury, Matthew
Abstract: Social support from a spouse, long-term partner, or someone who provides emotional or instrumental support may protect against consequences of aging, including mediating behavioral stress reactivity and altering neurobiological process that underlie short-term stress responses. Therefore, long-term social bonding may have behavioral and neurobiological benefits. The socially monogamous prairie vole provides a valuable experimental model for investigating the benefits of long-term social bonds on short-term stress reactivity in aging animals, given their unique social structure of forming enduring opposite-sex bonds, living in family groups, and bi-parental rearing strategies. Male-female pairs of long-term, cohabitating prairie voles were investigated for short-term behavioral and neuroendocrine stress reactivity following either long-term social pairing (control), or a period of social isolation. In Experiment 1, social isolation was associated with altered behavioral reactivity to an acute swim stressor, and greater neural activation in the hypothalamic paraventricular nucleus, as well as specifically the parvocellular region, following the swim stressor (vs. control). In Experiment 2, social isolation was associated with greater corticosterone reactivity following an acute restraint stressor (vs. control). No sex differences were observed. Exploratory correlation and subgroup analyses revealed systematic relationships among various demographic variables (such as age of the subjects, amount of time the pair cohabitated together, and number of litters the pair reared together) and the behavioral and neuroendocrine outcome measures. These findings may inform our understanding of the benefits of long-term social bonding on modulating short-term behavioral and neuroendocrine responses to stress. LAY SUMMARY: Receiving social support from a long-term spouse or partner, or having a strong support network from friends, may have important health benefits as people age. In aging monogamous prairie voles, social isolation from a long-term social partner disrupted behaviors and short-term stress responses, whereas living with a long-term partner protected against these disruptions. This research is important for our understanding of the benefits of social support on stress responses as we age.